Efficient extraction of essential oil from Cinnamomum burmannii leaves using enzymolysis pretreatment and followed by microwave-assisted method. (July 2021) - Liu, Zaizhi; Li, Hualan; Cui, Guoqiang; Wei, Mengxia; Zou, Zhengrong; Ni, Haiyan
Abstract: An enzymolysis–pretreatment microwave-assisted extraction (EP-MAE) method, namely enzymolysis pretreatment with enzyme mixtures (hemicellulase and cellulase) and followed by microwave irradiation, was developed to obtain essential oil from Cinnamomum burmannii leaves. Plackett–Burman design (PBD) and Box–Behnken design (BBD) were employed for the optimization of the EP-MAE procedure. The optimum EP-MAE conditions led to a significant higher essential oil yield than those of microwave-assisted extraction and hydrodistillation. Mass transfer kinetics curves revealed that EP-MAE possessed highest mass transfer coefficient than the reference methods owing to the combined treatment of enzymatic pretreatment and microwave irradiation. The GC–MS analysis results revealed that the C. burmannii essential oil extracted by EP-MAE possessed high quality as evidenced by its higher percentage of oxygenated compounds (88.31%) compared to those obtained from microwave-assisted extraction (80.41%) and hydrodistillation (73.24%). The present study demonstrated that EP-MAE is an efficient method for C. burmannii essential oil extraction, which provides a promising paradigm for the separation of essential oil from aromatic plant materials. Highlights: Enzymolysis pretreatment-microwave assisted extraction (EP-MAE) method was proposed. Hemicellulose/cellulase mixture was screened for enzymolysis pretreatment. EP-MAE showed great promising for C. burmannii essential oil extraction. Plackett–Burman design and Box–Behnken design were used for process optimization. C. burmannii essential oil extracted by EP-MAE possessed high quality.